PERFORMANS REPRODUKSI SAPI PERANAKAN ONGOLE DAN PERANAKAN LIMOUSIN DI KECAMATAN PADANG KABUPATEN LUMAJANG - Muhammad Luqman Akriono; Sri Wahyuningsih; M Nur Ihsan (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
The purpose of this research was conducted to evaluate reproductive performance of Ongolecrossbreed cattle andLimousin crossbreed  inPadang, Lumajang Regency. The material used on this research were 50 heads of Limousin crossbreed cattle and 50 heads ofOngole crossbreed cattle.The method used in this research was purposive sampling survey.The data were analyzed by t-test unpaired on Service per Conception (S/C), Days Open (DO), Calving Interval (CI).Conception Rate (CR) and Fertility Index (FI)were analyzed by descriptive.The results showed thatS/C, DO, CR, CI and FI of Ongole crossbreed cattle were 1,42±0,70; 107,34±32,38days, 70%; 399,04±39,97 days;66,95and for Limousine crossbreed were 1,62±0,76; 107,34±32,38days, 52%; 416,04±44,09days;26,80, respectively.  It was concluded that there was difference of reproductive performance between Ongole crossbreed cattle and Limousine crossbreed  and  reproductive performance of Ongole crossbreed cattle was better than Limousine crossbreed cattle. Keywords: Reproductive performance, Ongole crossbreed Cattle,Limousin crossbreed Cattle